Making Of Red Ginger Capsule Supplements For The Treatment Of Primary Dymenorore - Mesrida Simarmata (Science Midwifery, 2022)
Primary dysmenorrhea is physiological menstrual pain that occurs in women at the beginning of the menstrual cycle. Primary dysmenorrhea can be overcome using herbal plants such as red ginger. In the process of making red ginger capsules, it must meet the standards in order to keep the red ginger content intact. The purpose of this study was to determine the process of making red ginger capsule supplements as a treatment for primary dysmenorrhea. Research method: Descriptive that is to describe the process of making red ginger capsule supplements. Starting with red ginger made into powder, extract and capsules. The content, characteristics of simplicia and extract were identified and then made into capsules according to the dosage and tested for standardization. The results: The red ginger simplicia content met the requirements, the characteristics of the simplicia, red ginger powder and extract contain phenolic compounds such as saponins, flavonoids and steroids/triterpenoids which will be converted into oleoresin which contains the chemical gingerol as an anti-inflammatory in the treatment of dysmenorrhea, red ginger capsule supplements contain red ginger extract 50 mg. Conclusion: The process of making red ginger capsule supplements has met the standard